2015
DOI: 10.1017/cjn.2015.292
|View full text |Cite
|
Sign up to set email alerts
|

Motor Cortex Stimulation for Neuropathic Pain: A Randomized Cross-over Trial

Abstract: Background: Chronic motor cortex stimulation (MCS) has been used to treat medically refractory neuropathic pain over the past 20 years. We investigated this procedure using a prospective multicentre randomized blinded crossover trial. Methods: Twelve subjects with three different neuropathic pain syndromes had placement of MCS systems after which they were randomized to receive low ("subtherapeutic") or high ("therapeutic") stimulation for 12 weeks, followed by a crossover to the other treatment group for 12 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 32 publications
(45 reference statements)
0
24
0
Order By: Relevance
“…Some researchers suggest that MCS is suitable in chronic, permanent pain but not in paroxysmal pain, when DREZotomy should be used [7,19].…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers suggest that MCS is suitable in chronic, permanent pain but not in paroxysmal pain, when DREZotomy should be used [7,19].…”
Section: Discussionmentioning
confidence: 99%
“…Programing MCS can be a time‐consuming process and a failure to find the optimal stimulation settings could be a contributing factor to the lack of efficacy reported in number of recent publications . Previously, our team published an algorithm for programming MCS in which we suggested using 60% of the Motor Threshold (60 PMT) as the starting voltage and then adjusting the voltage up (e.g., 65 PMT) or down (e.g., 55 PMT) depending on the individual's response .…”
Section: Discussionmentioning
confidence: 99%
“…Case series , retrospective cohort studies , open label trials , and prospective, randomized, double‐blinded trials have demonstrated the efficacy of MCS in the treatment of patients with neuropathic pain of heterogeneous etiologies. More recently, however, two RCTs failed to demonstrate the efficacy of this therapy and several have cautioned against the use of this surgical procedure for pain management . If MCS is effective for neuropathic pain, then why does the therapy not work every time or in all centers?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later results have shown mixed success. Two studies have effectively reported MCS to be ineffective, but are hampered by issues surrounded by patient retention, patient selection, and administration of the treatment [127,128]. Lefaucher et al reported an RCT of MCS for peripheral neuropathic pain, where 13 patients had a significant reduction in some measurements of pain when the device was ‘on’ compared to ‘off’.…”
Section: Motor Cortex Stimulation and Its Comparison With Deep Bramentioning
confidence: 99%